Heat-dissipating silicone composition and method for producing the same

JP2025030910APending Publication Date: 2025-03-07SHIN ETSU CHEMICAL CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2023136602
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0025】 本発明の製造方法により製造される放熱性シリコーン組成物は、吐出性などの実装性能に優れ、耐ズレなどの信頼性が高く、機器に追従して高い放熱性能を発揮するとともに、機器の発する電磁波ノイズを抑制する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030910000001
    Figure 2025030910000001
  • Figure 2025030910000002
    Figure 2025030910000002
  • Figure 2025030910000003
    Figure 2025030910000003
Patent Text Reader

Abstract

To provide a silicone composition having excellent mountability and reliability and having both heat dissipation properties and electromagnetic wave absorption properties and a method for producing the same.SOLUTION: There is provided a heat-dissipating silicone composition in the form of a paste in which a cross-linked structure is formed, which comprises an addition reaction product of the following component (A) and component (B) and the following components (C), (D) and (E): (A) an organopolysiloxane having an alkenyl group bonded to a silicon atom and no alkoxy group bonded to a silicon atom at the molecular chain terminal, (B) an organohydrogen polysiloxane having a hydrogen atom bonded to a silicon atom, (C) a thermally conductive filler, (D) an electromagnetic wave absorbing filler and (E) a hydrosilylation reaction catalyst.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-dissipating silicone composition and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, heat-dissipating silicone greases based on silicone oil and containing various heat-dissipating fillers have been known (for example, Patent Document 1).

[0003] These heat-dissipating silicone greases have excellent workability, such as dispensing and screen printing, and they flexibly follow heat sources such as elements to exhibit high heat dissipation performance. However, when used over a long period of time, problems can arise such as pump-out and displacement from the element, making it impossible to maintain their heat dissipation properties.

[0004] As a means of solving these problems, a method has been proposed in which a thermally conductive filler is incorporated into partially crosslinked silicone (Patent Documents 2 and 3), but since partially crosslinked silicone is difficult to mix with the filler, it is difficult to obtain a paste-like composition, and it is also difficult to adjust the viscosity to a desired level.

[0005] Many curable materials have been proposed as materials that maintain heat dissipation performance over a long period of time (e.g., Patent Documents 4 and 5). These materials have excellent discharge properties and, because they are in a liquid state during the mounting process, they flexibly conform to the elements and exhibit high heat dissipation performance. In addition, because they harden, they have excellent long-term reliability.

[0006] However, these materials require several steps before they can be mounted. For example, one-component curing materials often require refrigeration or freezing, and a process of thawing to room temperature and a process of heating and curing are required before mounting. On the other hand, two-component curing materials can be stored and cured at room temperature, but the two liquid components must be precisely metered and mixed.

[0007] In order to overcome the problems described above, heat dissipating silicone compositions that are excellent in mountability, storage stability, and reliability have been proposed (for example, Patent Document 6).

[0008] Next, we will discuss electromagnetic wave absorption performance. With the development of information technology, electronic devices that use electromagnetic waves have become widespread in society. For example, wireless LAN, mobile phones, portable information terminals, road information systems, driving support systems, etc., are being used, and the electromagnetic waves used are shifting to the high frequency range.

[0009] On the other hand, as these electronic devices and technologies become more widespread, problems have arisen in that the electromagnetic waves they emit affect other electronic devices, causing them to malfunction. Therefore, electronic devices are required to not emit unwanted electromagnetic waves as much as possible, or not to malfunction even when exposed to electromagnetic waves, and technologies are being developed to give devices the ability to absorb and block electromagnetic waves.

[0010] Conventional blocking technologies that utilize electromagnetic wave reflection, such as metal alloy thin films and plates, are effective in blocking external electromagnetic noise and preventing leakage, but they can cause reflection and scattering inside equipment, resulting in adverse effects due to the proliferation of electromagnetic noise.

[0011] On the other hand, electromagnetic wave absorbing materials using soft magnetic metal fillers or ferrite fillers are highly effective in suppressing and preventing leakage of electromagnetic noise, and their development is being actively promoted (Patent Documents 7 and 8). However, most of the electromagnetic wave absorbing materials are designed to be molded into sheets.

[0012] Molded sheets have poor conformability to equipment, and therefore may not be able to fully demonstrate their electromagnetic wave absorption performance. In addition, while they are easy to handle, they are poorly suited to automatic mounting on devices using equipment. Although there are pick-and-place type machines that can handle this, they are generally large, making their introduction difficult, and there are also problems with the accuracy of sheet placement. Furthermore, if unexpected electromagnetic noise occurs, it is necessary to start over from scratch, including the design of the sheet shape, which also limits the freedom of design of the equipment. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Japanese Patent Application Publication No. 3-162493 [Patent Document 2] Japanese Patent Application Publication No. 04-268376 [Patent Document 3] JP 2002-294269 A [Patent Document 4] Patent 6791672 [Patent Document 5] Patent Publication No. 2022-029985 [Patent Document 6] Patent 6705426 [Patent Document 7] Patent 4699388 [Patent Document 8] JP 2021-174889 A Summary of the Invention [Problem to be solved by the invention]

[0014] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a silicone composition that combines excellent mountability and reliability with heat dissipation and electromagnetic wave absorption properties, and a method for producing the same. [Means for solving the problem]

[0015] The present invention relates to a paste-like heat-dissipating silicone composition having a crosslinked structure, the heat-dissipating silicone composition comprising an addition reaction product of the following components (A) and (B), and the following components (C), (D), and (E): (A) an organopolysiloxane having alkenyl groups bonded to silicon atoms and no alkoxy groups bonded to silicon atoms at the molecular chain terminals; (B) an organohydrogenpolysiloxane having hydrogen atoms bonded to silicon atoms; (C) Thermally conductive filler (D) electromagnetic wave absorbing filler, and (E) Hydrosilylation reaction catalyst to provide.

[0016] The heat dissipating silicone composition of the present invention has excellent mounting performance such as ejection properties, is highly reliable in terms of resistance to misalignment, and exhibits high heat dissipation performance by conforming to the device, while also suppressing electromagnetic noise emitted by the device.

[0017] Furthermore, the heat dissipating silicone composition of the present invention preferably contains an alkoxy group-containing organopolysiloxane (F) represented by the following general formula (5) as a wettability enhancer. [ka] (In the formula, R 6 are independently unsubstituted or substituted monovalent hydrocarbon radicals; R 7 are independently an alkyl group, and x is a positive number from 5 to 120.

[0018] In such heat-dissipating silicone compositions, the wettability improver is a component that improves the wettability of the components (C) and (D) with the components (A) and (B), and the improved wettability also improves the thermal conductivity of the heat-dissipating silicone composition.

[0019] In this case, the heat dissipating silicone composition of the present invention is 100 parts by mass of the component (A), the component (B), in which the amount of hydrogen atoms bonded to silicon atoms is 0.2 to 2.0 moles per mole of alkenyl groups bonded to silicon atoms in the component (A); the total amount of the components (C) and (D) is 30 to 90 volume % relative to 100 volume % of the total of the components (A) to (F), and the amount of the component (D) is 20 volume % or more; the component (E) in an amount of 0.1 to 1,000 ppm based on the mass of platinum atoms relative to the component (A); and The component (F) is present in an amount of 0.1 to 1000 parts by mass per 100 parts by mass of the total of the components (A) and (B). It is preferred that the compound contains

[0020] The heat dissipating silicone composition of the present invention can have such a blending ratio, for example.

[0021] The heat-dissipating silicone composition of the present invention is produced by a method for producing the heat-dissipating silicone composition, the method comprising the following steps (1) to (3): (1) a step of uniformly mixing the (A) to (E) components to obtain a paste-like composition; (2) heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, and then subjecting it to shear mixing to obtain the heat-dissipating silicone composition. to provide.

[0022] In the present invention, the composition can be produced in this manner.

[0023] The heat-dissipating silicone composition of the present invention can be produced by a method for producing the heat-dissipating silicone composition, the method comprising the following steps (1) to (3): (1) a step of uniformly mixing the components (A) to (F) to obtain a paste-like composition; (2) heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, and then subjecting it to shear mixing to obtain the heat-dissipating silicone composition. to provide.

[0024] The heat-dissipating silicone composition of the present invention can be produced in this manner when it contains a wettability enhancer. Effect of the Invention

[0025] The heat dissipating silicone composition produced by the production method of the present invention has excellent mounting performance such as ejection properties, is highly reliable in terms of resistance to misalignment, and conforms to the device to exhibit high heat dissipation performance, while also suppressing electromagnetic noise emitted by the device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] As described above, there has been a need for the development of a silicone composition that combines excellent mountability and reliability with heat dissipation and electromagnetic wave absorption properties, and a method for producing the same.

[0027] As a result of extensive investigations into the above problems, the present inventors have found that a composition obtained by a specific blending composition and production method can solve the above problems, and have completed the present invention.

[0028] That is, the present invention relates to a paste-like heat-dissipating silicone composition having a crosslinked structure, the heat-dissipating silicone composition comprising an addition reaction product of the following components (A) and (B), and the following components (C), (D), and (E): (A) an organopolysiloxane having alkenyl groups bonded to silicon atoms and no alkoxy groups bonded to silicon atoms at the molecular chain terminals; (B) an organohydrogenpolysiloxane having hydrogen atoms bonded to silicon atoms; (C) Thermally conductive filler (D) electromagnetic wave absorbing filler, and (E) A hydrosilylation reaction catalyst.

[0029] The present invention is described in detail below, but is not limited thereto. First, the components contained in the heat dissipating silicone composition (hereinafter also referred to as the heat dissipating silicone grease composition) are described.

[0030] <Heat dissipating silicone grease composition> The heat-dissipating silicone composition of the present invention is a paste-like heat-dissipating silicone composition in which a crosslinked structure has been formed, and contains an addition reaction product of the following components (A) and (B), and the following components (C), (D), and (E):

[0031] -(A) Organopolysiloxane- The organopolysiloxane of component (A) is an organopolysiloxane having alkenyl groups bonded to silicon atoms and no alkoxy groups bonded to silicon atoms at the molecular chain terminals, and contains more than one alkenyl group bonded to a silicon atom on average in one molecule, preferably 0.01 to 5 mol %, and more preferably 0.012 to 3 mol % of the total organic groups. The alkenyl groups bonded to silicon atoms may be present at either the molecular chain terminals or non-terminals, or both, in the organopolysiloxane molecule, but are preferably present only at both molecular chain terminals in order to improve flexibility.

[0032] There are no particular limitations on the molecular structure of the organopolysiloxane of this component, and examples include straight-chain and branched-chain structures.

[0033] The kinematic viscosity of the organopolysiloxane of this component at 25°C is not particularly limited, but is usually in the range of 100 to 1,000,000 mm 2 / s, which improves the stability of the silicone grease composition and facilitates mixing with components (B), (C), and (D) described below, and is therefore preferably 500 to 100,000 mm 2 The kinematic viscosity is a value measured by an Ostwald meter at 25°C.

[0034] The alkenyl group bonded to the silicon atom has a carbon atom number of usually 2 to 10, and preferably 2 to 6. Specific examples thereof include a vinyl group, an allyl group, a 1-butenyl group, and a 1-hexenyl group, with the vinyl group being preferred from the viewpoints of ease of synthesis and economy.

[0035] The organic group bonded to the silicon atom other than the alkenyl group bonded to the silicon atom is an unsubstituted or substituted monovalent hydrocarbon group having usually 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms. Specific examples thereof include alkyl groups such as methyl group, ethyl group, propyl group, butyl group, hexyl group, dodecyl group; aryl groups such as phenyl group; aralkyl groups such as 2-phenylethyl group, 2-phenylpropyl group; and chloromethyl group, 3,3,3-trifluoropropyl group, etc. in which part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as chlorine atom and fluorine atom. Among these, from the viewpoints of ease of synthesis and economy, preferably, they are methyl group and phenyl group, and particularly, 80 mol% or more, especially 90 mol% or more of all the organic groups other than the alkenyl group bonded to the silicon atom are methyl groups.

[0036] The organopolysiloxane of this component is, for example, represented by the following average composition formula (1): R a R 1 b SiO (4-a-b) / 2 (1) (In the formula, R is independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, R 1 is independently an alkenyl group, a is a number of 0 ≦ a < 2.2, b is a number of 0 < b ≦ 2.2, provided that a + b is a number of 1.8 to 2.2) and is represented by

[0037] In the above average composition formula (1), the unsubstituted or substituted monovalent hydrocarbon group represented by R usually has 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms. Specific examples thereof include those exemplified as the unsubstituted or substituted monovalent hydrocarbon group in the organic group bonded to the silicon atom.

[0038] R 1 The alkenyl group represented by has usually 2 to 10 carbon atoms, preferably 2 to 6 carbon atoms. Specific examples thereof include those exemplified as the alkenyl group bonded to the silicon atom.

[0039] The organopolysiloxane of this component is preferably, for example, a compound represented by the following general formula (2):

[0040] [ka] (In the formula, R 2 are independently unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds, R 3 are independently unsubstituted or substituted monovalent hydrocarbon radicals, provided that R 3 At least one of the groups is an alkenyl group, and m is a positive number of 50 to 3,000. It is expressed as:

[0041] In the above general formula (2), R 2 The number of carbon atoms in the unsubstituted or substituted monovalent hydrocarbon group represented by the following formula (I) is usually 1 to 20, and preferably 1 to 6. Specific examples thereof include those exemplified as the unsubstituted or substituted monovalent hydrocarbon group in the above-mentioned silicon-bonded organic group other than the silicon-bonded alkenyl group.

[0042] R 3 The number of carbon atoms in the unsubstituted or substituted monovalent hydrocarbon group represented by the following formula (I) is usually 1 to 20, and preferably 1 to 6. Specific examples thereof include those exemplified as the unsubstituted or substituted monovalent hydrocarbon group in the organic group bonded to a silicon atom other than the above-mentioned alkenyl group bonded to a silicon atom, and those exemplified as the above-mentioned alkenyl group bonded to a silicon atom.

[0043] m is preferably a positive number from 100 to 2,000, and more preferably from 150 to 1,500.

[0044] Specific examples of the organopolysiloxane of this component include the following (I) to (III):

[0045] [ka] (wherein m is the same as above)

[0046] [ka] (wherein, m1 and m2 are positive numbers that satisfy m=m1+m2)

[0047] [ka] (wherein, m1 and m3 are positive numbers that satisfy m=m1+m3) and the like, and preferably, the organopolysiloxanes represented by formula (I) or formula (II) are used.

[0048] The organopolysiloxane of component (A) may use either a single compound, or a combination of two or more different compounds.

[0049] -(B) Organohydrogenpolysiloxane- The organohydrogenpolysiloxane of component (B) has hydrogen atoms bonded to silicon atoms in the molecule, and preferably has at least 2 hydrogen atoms bonded to silicon atoms in one molecule, and more preferably 2 to 30. The hydrogen atoms bonded to silicon atoms may be present either at the molecular chain terminals or non-terminals in the organohydrogenpolysiloxane molecule, or may be present in both locations.

[0050] There are no particular limitations on the molecular structure of the organohydrogenpolysiloxane of this component, and examples include straight-chain and branched-chain structures.

[0051] The kinematic viscosity of the organohydrogenpolysiloxane of this component at 25°C is not particularly limited, but is usually in the range of 10 to 300 mm 2 / s, preferably 20 to 200 mm 2 / s.

[0052] The organic groups bonded to the silicon atom other than the hydrogen atoms bonded to the silicon atom are usually unsubstituted or substituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms. Specific examples thereof include alkyl groups such as methyl group, ethyl group, propyl group, hexyl group, octyl group, decyl group, dodecyl group, tetradecyl group, hexadecyl group, octadecyl group; cycloalkyl groups such as cyclopentyl group, cyclohexyl group; alkenyl groups such as vinyl group, allyl group; aryl groups such as phenyl group, tolyl group; aralkyl groups such as 2-phenylethyl group, 2-methyl-2-phenylethyl group; halogenated hydrocarbon groups such as 3,3,3-trifluoropropyl group, 3-(perfluorobutyl)ethyl group, 2-(perfluorooctyl)ethyl group, p-chlorophenyl group in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as chlorine atom and fluorine atom. Among these, from the viewpoints of ease of synthesis and economy, preferably, 90 mol% or more of all the organic groups other than the hydrogen atoms bonded to the silicon atom are methyl groups.

[0053] The organohydrogenpolysiloxane of this component is, for example, represented by the following average compositional formula (3): R 4 c H d SiO (4-c-d) / 2 (3) (In the formula, R 4 is independently an unsubstituted or substituted monovalent hydrocarbon group, c is a number satisfying 0 ≦ c < 3, d is a number satisfying 0 < d ≦ 3, provided that c + d is a number satisfying 0 < c + d ≦ 3) is represented by.

[0054] In the above average compositional formula (3), the unsubstituted or substituted monovalent hydrocarbon group represented by R 4 usually has 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms. Specific examples thereof include those exemplified as the unsubstituted or substituted monovalent hydrocarbon groups in the organic groups bonded to the silicon atom other than the hydrogen atoms bonded to the silicon atom, and preferably include methyl group, ethyl group, propyl group, and phenyl group.

[0055] The organopolysiloxane of this component is preferably, for example, a compound represented by the following general formula (4):

[0056] [ka] (In the formula, n is a number from 5 to 200, and R 5 are independently a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group, provided that at least two of them are hydrogen atoms. It is expressed as:

[0057] In the above general formula (4), R 5 The number of carbon atoms in the unsubstituted or substituted monovalent hydrocarbon group represented by the following formula (I) is usually 1 to 20, and preferably 1 to 6. Specific examples thereof include those exemplified as the unsubstituted or substituted monovalent hydrocarbon group in (A) in the organic group bonded to a silicon atom other than a hydrogen atom bonded to the silicon atom.

[0058] n is preferably a number from 10 to 100, and more preferably 15 to 90.

[0059] The amount of component (B) added is such that the number of hydrogen atoms bonded to silicon atoms in the organohydrogenpolysiloxane molecules of component (B) is preferably 0.2 to 2.0 moles, more preferably 0.5 to 1.5 moles, and particularly preferably 0.7 to 1.2 moles per mole of alkenyl groups bonded to silicon atoms in the organopolysiloxane molecules of component (A).

[0060] The organohydrogenpolysiloxane of component (B) may use either a single compound, or a combination of two or more different compounds.

[0061] -(C) Thermally conductive filler- The thermally conductive filler, which is the component (C), is a component for imparting thermal conductivity to the composition. This thermally conductive filler is not particularly limited, but is preferably one having good thermal conductivity, and specific examples thereof include aluminum powder, zinc oxide powder, alumina powder, boron nitride powder, aluminum nitride powder, aluminum hydroxide powder, magnesium oxide powder, silicon nitride powder, copper powder, silver powder, diamond powder, nickel powder, zinc powder, stainless steel powder, carbon powder, etc.

[0062] The thermally conductive filler of this component is not particularly limited, and may be, for example, spherical particles or a mixture of particles of various shapes with no particular shape. The average particle size of the thermally conductive filler is not particularly limited, but is preferably 0.1 to 200 μm, more preferably 1 to 100 μm, since this provides a uniform composition with particularly excellent viscosity and extensibility.

[0063] -(D) Electromagnetic wave absorbing filler- The electromagnetic wave absorbing filler, which is the component (D), is a component for imparting electromagnetic wave absorbing properties to the composition. The electromagnetic wave absorbing filler is not particularly limited, but may be used according to the required absorption frequency band. Examples of the soft magnetic metal powder include Fe-Ni, Fe-Co, Fe-Cr, Fe-Si, Fe-Al, Fe-Cr-Si, Fe-Cr-Al, and Fe-Al-Si alloys. Examples of the phyllite filler include spinel phyllite such as MnFe2O4, CoFe2O4, NiFe2O4, CuFe2O4, ZnFe2O4, MgFe2O4, and Fe3O4, and Ba2Co2Fe 12 O 22 , Ba2Ni2Fe 12 O 22 , Ba2Zn2Fe 12 O 22 , Ba2Mn2Fe 12 O 22 , Ba2Mg2Fe 12 O 22 , Ba2Cu2Fe 12 O 22 , Ba3Co2Fe 24 O 41 Examples of hexagonal phyllite include:

[0064] The electromagnetic wave absorbing filler of this component is not particularly limited, and may be, for example, spherical particles, scaly particles, or a mixture of particles of various shapes with no particular shape. The average particle size of the electromagnetic wave absorbing filler is not particularly limited, but is preferably 0.1 to 100 μm, more preferably 1 to 30 μm, since it is particularly excellent in ejection property and spreadability and a uniform composition can be obtained.

[0065] The above average particle size is usually the cumulative volume average diameter D 50 Specifically, it can be calculated as the cumulative 50% particle diameter (D) on a volume basis measured using a particle size distribution analyzer MT3000II manufactured by Microtrack Bell Co., Ltd. 50 ) value.

[0066] The total amount of components (C) and (D) is preferably 30 to 90 volume %, more preferably 40 to 85 volume %, and even more preferably 70 to 80 volume %, of which the total of components (A) to (D) and component (E) described below, and component (F) described below if included, is 100 volume %, and of this, the amount of component (D) is 20 volume % or more, more preferably 30 volume % or more. If this range is satisfied, the thermal conductivity and electromagnetic wave absorption performance of the composition will be excellent.

[0067] The thermally conductive filler of component (C) may use either a single material, or a combination of two or more different materials.

[0068] The electromagnetic wave absorbing filler of component (D) may use either a single material, or a combination of two or more different materials.

[0069] -(E) Hydrosilylation reaction catalyst- The hydrosilylation catalyst, which is component (E), is a component that promotes the formation of a crosslinked structure by the addition reaction between components (A) and (B). As the hydrosilylation catalyst, a conventionally known catalyst can be used, and examples thereof include platinum alone, platinum compounds such as chloroplatinic acid, platinum-olefin complexes, and platinum-alcohol complexes.

[0070] The blend amount of component (E) is preferably 0.1 to 1,000 ppm, and especially 1 to 500 ppm, based on the mass of platinum atoms relative to the organopolysiloxane of component (A).

[0071] The hydrosilylation reaction catalyst of the component (E) may use either a single compound, or a combination of two or more different compounds.

[0072] -Other ingredients- In addition to the components (A) to (E), the following other components may be blended as necessary. These other components may be used alone or in combination of two or more.

[0073] <Wettability improver> The wettability enhancer is a component for improving the wettability of the components (C) and (D) with respect to the components (A) and (B), and the improved wettability also improves the thermal conductivity of the composition. Specific examples of the wettability enhancer include alkoxysilane and the component (F) represented by the following general formula (5):

[0074] [ka] (In the formula, R 6 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 7 are independently an alkyl group, and x is a positive number from 5 to 120. Examples of suitable organosiloxanes include alkoxy group-containing organopolysiloxanes (hydrolyzable organopolysiloxanes having a trifunctional molecular chain at one end) represented by the following formula:

[0075] In the above general formula (5), R 6The number of carbon atoms in the unsubstituted or substituted monovalent hydrocarbon group represented by the formula (I) is usually 1 to 20, preferably 1 to 18, and more preferably 1 to 6. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl; cyclohexyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl and tolyl; aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl; and halogenated hydrocarbon groups in which some or all of the hydrogen atoms in these groups are substituted with halogen atoms such as chlorine and fluorine, such as 3,3,3-trifluoropropyl, 2-(perfluorobutyl)ethyl, 2-(perfluorooctyl)ethyl, and p-chlorophenyl, and are preferably methyl and vinyl groups.

[0076] R 7 The number of carbon atoms in the alkyl group represented by the formula (I) is usually 1 to 6. Specific examples thereof include a methyl group, an ethyl group, and a propyl group, and preferably a methyl group or an ethyl group.

[0077] x is preferably a positive number of 10 to 90, and more preferably 15 to 80.

[0078] Examples of the alkoxysilane include those represented by the following general formula (6): R 8 y R 9 z Si(OR 10 ) 4-y-z (6) (In the formula, R 8 are independently unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds, R 9 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 10 are independently an alkyl group, y is an integer of 0 to 2, preferably 1, and z is an integer of 0 to 2, preferably 0 or 1, with the proviso that y+z is 1 or 2. Examples of the alkoxysilane include those represented by the following formula:

[0079] In the above general formula (6), R 8 The unsubstituted or substituted monovalent hydrocarbon group represented by the formula (I) is a linear alkyl group having usually 6 to 15 carbon atoms, preferably 8 to 12 carbon atoms. When this range is satisfied, the wettability of components (C) and (D) is improved, and the handling of this component is also improved. Specific examples include alkyl groups such as hexyl, octyl, nonyl, decyl, dodecyl, and tetradecyl.

[0080] R 9 The number of carbon atoms in the monovalent hydrocarbon group represented by the formula (I) is usually 1 to 8, and preferably 1 to 6. Specific examples thereof include alkyl groups, cycloalkyl groups, and alkenyl groups, and more specifically, for example, alkyl groups such as methyl groups, ethyl groups, propyl groups, hexyl groups, and octyl groups; cycloalkyl groups such as cyclopentyl groups and cyclohexyl groups; alkenyl groups such as vinyl groups and allyl groups; aryl groups such as phenyl groups and tolyl groups; aralkyl groups such as 2-phenylethyl groups and 2-methyl-2-phenylethyl groups; and halogenated hydrocarbon groups such as 3,3,3-trifluoropropyl groups, 2-(nanofluorobutyl)ethyl groups, 2-(heptadecafluorooctyl)ethyl groups, and p-chlorophenyl groups in which some or all of the hydrogen atoms in these groups are substituted with halogen atoms such as chlorine atoms and fluorine atoms, and preferably, methyl groups, ethyl groups, vinyl groups, and phenyl groups.

[0081] R 10 The number of carbon atoms in the alkyl group represented by the formula (I) is usually 1 to 6. Specific examples thereof include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group, and preferably a methyl group or an ethyl group.

[0082] Specific examples of the alkoxysilane represented by the above formula (6) include C6H 13 Si(OCH3)3, C 10 H 21 Si(OCH3)3, C 12 H 25 Si(OCH3)3, C12 H 25 Si(OC2H5)3, C 10 H 21 Si(CH3)(OCH3)2, C 10 H 21 Si(C6H5)(OCH3)2, C 10 H 21 Si(CH3)(OC2H5)2, C 10 H 21 Si(CH=CH2)(OCH3)2, C 10 H 21 Examples include Si(CH2CH2CF3)(OCH3)2.

[0083] The amount of the wettability enhancer is preferably 0.1 to 1000 parts by mass, more preferably 0.5 to 600 parts by mass, and even more preferably 100 to 550 parts by mass, relative to 100 parts by mass of the total of the components (A) and (B). When this range is satisfied, the wettability of the components (C) and (D) is good.

[0084] <Reaction control agent> The reaction inhibitor is a component that is preferably used to control and suppress the rate of progress of the addition reaction between the (A) component and the (B) component, and to obtain a uniform composition. Specific examples thereof include acetylene compounds, nitrogen compounds, organic phosphorus compounds, oxime compounds, organic chloro compounds, etc. These reaction inhibitors are preferably used after being dissolved in an organic solvent such as toluene, xylene, isopropyl alcohol, etc., in order to improve the dispersibility in the composition.

[0085] The amount of the reaction inhibitor added is preferably 0.01 to 1 part by mass, and more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the organopolysiloxane of the component (A).

[0086] <Non-reactive organopolysiloxane> The non-reactive organopolysiloxane is an organopolysiloxane that does not have a reactive group in the molecule, and is capable of suitably adjusting the viscosity and workability of the resulting composition. The molecular structure of this non-reactive organopolysiloxane is not particularly limited, and may be either linear or branched.

[0087] Examples of the reactive group include a hydrogen atom bonded to a silicon atom, a hydroxy group bonded to a silicon atom (i.e., a silanol group), an alkoxy group bonded to a silicon atom, an amino group, a carboxyl group, an epoxy group, a vinyl group, a mercapto group, and a methacryloxy group.

[0088] The non-reactive organopolysiloxane is not particularly limited, but dimethylpolysiloxane, phenylmethylpolysiloxane, and the like are preferred from an economical viewpoint.

[0089] The non-reactive organopolysiloxane preferably has a viscosity at 25°C of 10 to 1,000,000 mm 2 / s, more preferably 100 to 100,000 mm 2 / s.

[0090] The amount of the non-reactive organopolysiloxane added is preferably 0 to 50 parts by mass, and more preferably 0 to 30 parts by mass, per 100 parts by mass of the combined total of the components (A) and (B).

[0091] It is preferable that the present invention provides a heat dissipating silicone composition containing, for example, 100 parts by mass of the component (A); the component (B) in an amount such that hydrogen atoms bonded to silicon atoms are 0.2 to 2.0 moles per mole of alkenyl groups bonded to silicon atoms in the component (A); the sum of the components (C) and (D) is 30 to 90 volume%, assuming that the total of the components (A) to (F) is 100 volume%, and of this, the component (D) is an amount such that 20 volume% or more of the component (C) is present; the component (E) in an amount such that, based on the mass of platinum atoms, it is 0.1 to 1,000 ppm relative to the component (A); and the component (F) in an amount of 0.1 to 1,000 parts by mass relative to 100 parts by mass of the combined total of the components (A) and (B).

[0092] <Manufacturing method> The heat-dissipating silicone composition of the present invention comprises components (A) to (E) (or components (A) to (F)) (1) a step of uniformly mixing the components (A) to (E) (or the components (A) to (F)) to obtain a paste-like composition; (2) heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, and then subjecting it to shear mixing to obtain the heat-dissipating silicone composition. The present invention is produced by a method comprising the steps of:

[0093] The mixing includes, for example, mixing by stirring and kneading using a mixer or the like described below.

[0094] -Process (1)- Step (1) is a step of obtaining a paste-like composition in which the components (A) to (E) are uniformly mixed. This paste-like composition may be obtained in any manner, and may be obtained by mixing a mixture of the components (A) to (D) in advance with the component (E), or by mixing the components (A) to (E) at once. Specifically, for example, it can be obtained by the following method.

[0095] First, the components (A) to (D) are mixed by stirring together with a wettability improver (for example, component (F)), a non-reactive organopolysiloxane, etc., as necessary, and stirring is continued until the mixture is pasted to obtain a paste-like composition. In the stirring process up to this point, the mixture may be heated to about 50 to 200°C as necessary, but if heated, it is cooled to room temperature before adding the next component (E). If a reaction inhibitor is to be blended into the composition, the reaction inhibitor is then added to the obtained paste-like composition and stirred until it is uniformly mixed in the composition. Then, the component (E) is added to the obtained paste-like composition and stirred until the component (E) is uniformly dispersed in the composition.

[0096] -Process (2)- In step (2), the paste-like composition is heated and mixed to promote the hydrosilylation reaction and ripen. This step advances the reaction between components (A) and (B) and forms a crosslinked structure in the composition.

[0097] When the paste-like composition is heated and mixed at a temperature of 90° C. or higher, the hydrosilylation reaction proceeds at an appropriate rate, and it does not take a long time for the reaction to be completed (matured state). The heating and mixing is preferably performed at 90 to 200° C., more preferably at 120 to 180° C.

[0098] The heating and mixing time is until the maturation of the paste-like composition is completed, and is not particularly limited, but is usually 30 minutes to 5 hours, and preferably 1 to 3 hours in order to ensure maturation.

[0099] -Process (3)- Step (3) is a step in which the aged paste-like composition is cooled to a temperature of 50°C or less while standing, and then mixed under shear. This step yields the heat-dissipating silicone composition. Cooling may be achieved by natural heat dissipation or by a cooling device or the like. Mixing under shear may be achieved using a mixer such as a planetary mixer, a three-roller, a two-roller, a kneader, a disper, a Shinagawa mixer, a Supermascolloider, a trimix, or a twinmix, or a combination of these. Here, it is not necessary to apply a shear force in this step until the cooling temperature is reached.

[0100] When the cooling temperature is 50° C. or lower, sufficient shear force can be applied to the paste-like composition. Moreover, excessive cooling does not increase the shear force and improves workability, so the cooling is preferably performed to 0 to 50° C., more preferably to 10 to 40° C. By passing through this step (3), the viscosity and dischargeability of the composition can be adjusted.

[0101] The viscosity of the obtained composition is not particularly limited, but is, for example, 100 to 1000 Pa·s, and preferably 200 to 800 Pa·s. The viscosity is a value measured at 25° C. using a Malcolm viscometer. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is in no way limited to these examples. In the examples, the viscosity is measured at 25°C.

[0103] [Component (A)] (A-1) Linear chain with vinyl groups at both ends, kinematic viscosity 600 mm 2 / s dimethylpolysiloxane (Vi value: 0.015 mol / 100g, specific gravity: 1.0). (A-2) Linear chain with vinyl groups at both ends, kinematic viscosity 30,000 mm 2 / s dimethylpolysiloxane (Vi value: 0.00375 mol / 100g, specific gravity: 1.0).

[0104] [(B) Component] (B-1) The following average composition formula (7) [ka] Organohydrogenpolysiloxane (H value: 0.005 mol / g, specific gravity: 1.0).

[0105] (B-2) The following average composition formula (8) [ka] Organohydrogenpolysiloxane (H value: 0.0013 mol / g, specific gravity: 1.0) represented by the formula:

[0106] [(C) component] (C-1) Aluminum oxide powder (average particle size: 75 μm, specific gravity: 3.98) (C-2) Aluminum oxide powder (average particle size: 2 μm, specific gravity: 3.98) (C-3) Zinc oxide powder (average particle size: 0.25 μm, specific gravity: 5.67) (C-4) Aluminum hydroxide powder (average particle size: 1 μm: specific gravity: 2.42) (C-5) Magnesium oxide powder (average particle size: 90 μm, specific gravity: 3.58)

[0107] [(D) component] (D-1)Fe-Cr-Si soft magnetic powder (average particle size: 8μm, specific gravity: 7.90)

[0108] [(E) component] (E-1) A solution in which platinum-divinyltetramethyldisiloxane complex was dissolved in the same dimethylpolysiloxane as in (A-1) above (platinum atom content: 1 mass %, specific gravity: 1.0).

[0109] [Component (F)] (F-1) The following formula (9) [ka] Organopolysiloxane wettability improver (specific gravity: 1.0).

[0110] [(G) component] (G-1) Ethynylcyclohexanol reaction inhibitor (specific gravity: 1.0)

[0111] [Viscosity of composition] The viscosity of the composition was measured at 25°C using a rotational viscometer, and was measured using a Malcom viscometer (Type PC-10AA) manufactured by Malcom Co., Ltd.

[0112] [Thermal conductivity of the composition] The thermal conductivity of the composition was measured at 25° C. using a TPS-2500S manufactured by Kyoto Electronics Manufacturing Co., Ltd. by the hot disk method in accordance with ISO 22007-2.

[0113] [Extrusion property of composition] The dischargeability of the composition was evaluated by filling a 30 cc tipless syringe (Optimum, manufactured by Nordson Corporation) with the composition and discharging it under a pressure of 0.4 MPa for 60 seconds.

[0114] [Composition deviation test] A 0.25 mm spacer was provided, and the composition was sandwiched between an aluminum plate (80 mm x 50 mm) and a glass plate (80 mm x 50 mm) to form a circle with a diameter of 1.6 cm. The test piece was placed at 90° to the ground, and a 500-cycle test was performed using a thermal shock tester (model number: TSE-11-A) manufactured by Espec Corp., which was set to alternate between -40°C and 125°C (30 minutes each). After 500 cycles, the amount of displacement of the composition from its original position was measured. <Standards> If the difference is 2 mm or less, it can be said that the resistance to displacement is excellent.

[0115] [Appearance of composition after displacement test] The state of the composition after the above 500 cycles was observed. A state in which there were no voids or cracks in the composition was marked with ◯, and a state in which there were voids or cracks was marked with ×.

[0116] [Measurement of transmission attenuation rate of composition] To evaluate the electromagnetic wave absorption performance of the composition, the transmission attenuation rate Rtp from 1 GHz to 30 GHz was measured at a thickness of 1 mm using a microstrip line method conforming to IEC 62333. The transmission attenuation rate Rtp is expressed in dB, with a higher value indicating higher electromagnetic wave absorption performance. 3 dB means 50% absorption, 10 dB means 90% absorption, and 20 dB means 99% absorption, and a value of 10 dB or more is considered excellent.

[0117] <Examples 1 to 8> The components shown in Table 1 were charged and compositions were prepared according to the following procedure. Step (1): Components (A), (C), (D) and, if necessary, (F) were charged into a planetary mixer and mixed at room temperature until a paste was formed. Then, component (G) was added and mixed for 10 minutes, and component (E) was added and mixed for 10 minutes. Finally, component (B) was added and mixed for 10 minutes to complete step (1). Step (2): The paste-like composition obtained in step (1) was heated to 160°C and heated and stirred for 2 hours to promote the hydrosilylation reaction, and then heated and stirred for an additional hour for maturation to obtain a composition having a crosslinked structure. Step (3): The composition obtained in step (2) was cooled to room temperature and stirred at room temperature for 1 hour to complete the preparation of the composition.

[0118] The above-mentioned tests and measurements were carried out using the obtained composition, and the results are shown in Table 1.

[0119] [Table 1] *For convenience, the number of silicon-bonded hydrogen atoms in component (B) per silicon-bonded alkenyl group in component (A) is represented as H / Vi.

[0120] In Examples 1 to 8, the components (A) and (B) formed a crosslinked structure in the composition, and thus the displacement test showed a value of 2 mm or less, indicating excellent displacement resistance. In addition, even at high viscosity, the composition maintained dischargeability and was excellent in workability. The transmission attenuation rate Rtp was large, indicating high electromagnetic wave absorption performance.

[0121] <Comparative Examples 1 and 2> Each component was charged as shown in Table 2, and a composition was prepared. In Comparative Example 1, a composition was prepared in the same manner as in Examples, except that component (E) was not added. In Comparative Example 2, a composition was prepared in the same manner as in Examples, except that component (D) was not added.

[0122] In Comparative Example 1, the components (A) and (B) in the composition are not crosslinked (not an addition reaction product), so the composition has low viscosity and therefore high ejection properties, but low slippage resistance and low reliability. In addition, the transmission attenuation rate could not be measured because a uniform thickness could not be maintained. In Comparative Example 2, the component (D) was not included, so no clear transmission attenuation rate was detected.

[0123] [Table 2]

[0124] The present invention includes the following inventions.

[0125] [1]: A paste-like heat-dissipating silicone composition having a crosslinked structure, the heat-dissipating silicone composition comprising an addition reaction product of the following components (A) and (B), and the following components (C), (D), and (E): (A) an organopolysiloxane having alkenyl groups bonded to silicon atoms and no alkoxy groups bonded to silicon atoms at the molecular chain terminals; (B) an organohydrogenpolysiloxane having hydrogen atoms bonded to silicon atoms; (C) Thermally conductive filler (D) electromagnetic wave absorbing filler, and (E) A hydrosilylation reaction catalyst.

[0126] [2]: The heat-dissipating silicone composition according to the above [1], further comprising, as a wettability enhancer, an alkoxy group-containing organopolysiloxane (F) represented by the following general formula (5): [ka] (In the formula, R 6 are independently unsubstituted or substituted monovalent hydrocarbon radicals; R 7 are independently an alkyl group, and x is a positive number from 5 to 120.

[0127] [3]: 100 parts by mass of the component (A), the component (B), in which the amount of hydrogen atoms bonded to silicon atoms is 0.2 to 2.0 moles per mole of alkenyl groups bonded to silicon atoms in the component (A); the total amount of the components (C) and (D) is 30 to 90 volume % relative to 100 volume % of the total of the components (A) to (F), and the amount of the component (D) is 20 volume % or more; the component (E) in an amount of 0.1 to 1,000 ppm based on the mass of platinum atoms relative to the component (A); and The component (F) is present in an amount of 0.1 to 1000 parts by mass per 100 parts by mass of the total of the components (A) and (B). The heat dissipating silicone composition according to the above item (2), which contains

[0128] [4]: A method for producing a heat-dissipating silicone composition, comprising the following steps (1) to (3): (1) a step of uniformly mixing the (A) to (E) components to obtain a paste-like composition; (2) heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, followed by shear mixing to obtain the heat dissipating silicone composition according to the above-mentioned (1).

[0129] [5]: A method for producing a heat-dissipating silicone composition, comprising the following steps (1) to (3): (1) a step of uniformly mixing the components (A) to (F) to obtain a paste-like composition; (2) heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50°C or less, followed by shear mixing, to obtain the heat dissipating silicone composition described in [2] or [3] above.

[0130] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. A heat-dissipating silicone composition in the form of a paste having a crosslinked structure, the heat-dissipating silicone composition comprising an addition reaction product of the following components (A) and (B), and the following components (C), (D), and (E): (A) an organopolysiloxane having alkenyl groups bonded to silicon atoms and no alkoxy groups bonded to silicon atoms at the molecular chain terminals; (B) an organohydrogenpolysiloxane having hydrogen atoms bonded to silicon atoms; (C) Thermally conductive filler (D) an electromagnetic wave absorbing filler, and (E) A hydrosilylation reaction catalyst.

2. The heat-dissipating silicone composition according to claim 1, further comprising an alkoxy group-containing organopolysiloxane (F) represented by the following general formula (5) as a wettability improver: 【Chemistry 1】 (In the formula, R 6 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 7 are independently an alkyl group, and x is a positive number from 5 to 120.

3. 100 parts by mass of the component (A), the component (B) in an amount such that the amount of hydrogen atoms bonded to silicon atoms is 0.2 to 2.0 moles per mole of alkenyl groups bonded to silicon atoms in the component (A); the total amount of the (C) and (D) components is 30 to 90 volume % relative to 100 volume % of the total of the (A) to (F) components, and the (D) component is 20 volume % or more of the total amount; The component (E) is present in an amount of 0.1 to 1,000 ppm based on the mass of platinum atoms relative to the component (A); and The component (F) is present in an amount of 0.1 to 1000 parts by mass per 100 parts by mass of the total of the components (A) and (B). The heat dissipating silicone composition according to claim 2, which comprises

4. A method for producing a heat-dissipating silicone composition, comprising the following steps (1) to (3): (1) a step of uniformly mixing the components (A) to (E) to obtain a paste-like composition; (2) A step of heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, and then carrying out shear mixing to obtain the heat dissipating silicone composition according to claim 1.

5. A method for producing a heat-dissipating silicone composition, comprising the following steps (1) to (3): (1) a step of uniformly mixing the components (A) to (F) to obtain a paste-like composition; (2) A step of heating and mixing the paste-like composition to accelerate the hydrosilylation reaction and mature the composition, thereby obtaining a paste-like composition having a crosslinked structure; and (3) A step of cooling the aged paste-like composition to a temperature of 50° C. or less, and then carrying out shear mixing to obtain the heat-dissipating silicone composition according to claim 2.

Citation Information

Patent Citations

  • Greasy silicone composition and production thereof

    JP1992268376A

  • Electromagnetic wave-absorbing, thermally conductive silicone rubber composition

    JP2001294752A

  • Extrusible crosslinked grease-like radiation material, container in which the material is filled and enclosed, manufacturing method of the container and radiation method using these

    JP2002294269A

  • Electromagnetic wave absorbing heat-conductive silicone composition and molding thereof

    JP2005015679A

  • Extrudable crosslinked grease-like electromagnetic wave absorber, container packing and encapsulating absorber, method of manufacturing cotnainer, and method for electromagnetic wave absorption utilizing them

    JP2005286195A